2019
DOI: 10.3390/s19214710
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Air Pressure on the Dynamics of Flexural Ultrasonic Transducers

Abstract: The flexural ultrasonic transducer comprises a piezoelectric ceramic disc bonded to a membrane. The vibrations of the piezoelectric ceramic disc induce flexural modes in the membrane, producing ultrasound waves. The transducer is principally utilized for proximity or flow measurement, designed for operation at atmospheric pressure conditions. However, there is rapidly growing industrial demand for the flexural ultrasonic transducer in applications including water metering or in petrochemical plants where the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…To realise the advantages of FUTs for a broad range of metrology applications, different strategies have been proposed to increase resilience to increasing and fluctuating pressure levels. Recently, the authors have published research into the vented flexural ultrasonic transducer (VFUT) and its dynamic performance towards 100 bar in air [6,7]. It was shown that through removal of the hermetic seal and equalisation of pressure across the membrane of an FUT, reliable ultrasound measurements can be conducted in an air environment at relatively high levels of pressure.…”
Section: Introductionmentioning
confidence: 99%
“…To realise the advantages of FUTs for a broad range of metrology applications, different strategies have been proposed to increase resilience to increasing and fluctuating pressure levels. Recently, the authors have published research into the vented flexural ultrasonic transducer (VFUT) and its dynamic performance towards 100 bar in air [6,7]. It was shown that through removal of the hermetic seal and equalisation of pressure across the membrane of an FUT, reliable ultrasound measurements can be conducted in an air environment at relatively high levels of pressure.…”
Section: Introductionmentioning
confidence: 99%
“…The FUT operates by vibrating at one of the resonant modes of the platepiezoelectric disc composite structure, with a relatively high transduction efficiency at low power and low voltage (<10 V) excitation. The simple structure is easy to manufacture, resulting in a low cost, mechanically robust transducer [20][21][22][23][24][25][26][27][28][29]. One of the principal limitations of the FUT has been the assumption that operating frequency is generally limited to below 50 kHz, with the most common operation frequency for commercially available FUTs being 40 kHz [21].…”
Section: Introductionmentioning
confidence: 99%
“…A 20-60 kHz brick-wall band-pass filter was applied to the voltage responses in post-processing to eliminate noise, where the FFTs were computed using measured acoustic data. The series resonance frequency, or frequency of minimum impedance, of each transducer is then monitored as a function of the environmental pressure level, , extended from prior research [18]. The results are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Venting has also been demonstrated in forms of the piezoelectric micromachined ultrasonic transducer (PMUT) for purposes including the recycling of back-cavity pressure in the transducer [16,17]. Recently, we investigated the influence of air pressure on the dynamics of different flexural ultrasonic transducers, including a vented form of the CFUT [18]. We demonstrated fundamental ultrasound measurement principles for transducers operating in environments with elevated pressure levels and the reliability potential of the vented configuration.…”
Section: B Transducers For Environments Of Elevated Pressurementioning
confidence: 99%